Inviting performance into the English foreign language classroom - Ulrike Sievers (SCENARIO: Journal for Performative Teaching, Learning, Research, 2022)
In this article the foreign language classroom in a Waldorf school is described as a space inviting active performative participation. It gives examples spanning the lower, middle and particularly the upper school, in which performative methods and creativity are specifically encouraged. The aim is to involve the whole child and young person not only in reproducing but in producing actions in and through the foreign language, using methods such as enacting stories and pictures, producing and playing scenes, translating prose texts into scripts for plays, radio plays and story boards for film.